A relação homem e natureza, capitalismo e serviço social: considerações sobre os fundamentos da temática ambiental - Braz, Girlei da Rosa (2016)
This dissertation deals with the approach of elements of environmental issues, which can be understood as a basis for understanding the relationship between man and nature within capitalist society. It also sought to understand possible elements to be captured by the Social Work, towards a qualified, theoretical and practical approach at the issues surrounding the plots, contradictions and environmental degradation impacts on living conditions and fundamental rights guarantee. The methodology consists of a literature research of investigative nature, to provide knowledge about environmental issues. In this sense, we sought, in the first chapter, the approach of the ontological foundations of the relationship between man and nature, mediated by the work category. The second chapter aimed at demonstrating the criticism and assertions about social theory, especially regarding the social thought of Marx. Besides, it discusses the crisis of capital and, consequently, the environmental crisis, so as to show some resilience propositions of this crisis that has been advocated in recent times. The third part of this paper turns to Social Work, exploring mainly a topic of major relevance to the profession, given its pedagogical nature, which is the environmental education. The main result of this study confirms the thought that the environmental crisis follows a broader crisis, the structural crisis of capital. Thus, not only direct means of man's action on nature generate environmental degradation, but the whole social structure, especially in the capitalist mode of production, as a collective being and able to anticipate his actions. Thus, the environmental crisis is a refraction of the structural crisis of capital, but which permeates the problem of the inability of the capital to grow linearly and extends to a rationality crisis of a period which has mathematized all segments of life in Earth.